Formes de réception et d’appropriation des ressources numériques en milieu étudiant. - Mariangela Roselli (Tic & Société)
An ethnographical inquiry on the users of the university library of the University of Toulouse (France, literature and human sciences) carried out in 2007-2008 shows how students do with the Web environment and electronical resources. Two ethnographical scenes and two sociological portraits are presented to illustrate how computers and numerical resources have generated new practices in university library. The cases described in the paper develop some examples of the new rationalities in scientific research associated with the new environment. They clearly show that a foundamental teaching in numerical environment and research methodology is necessary.